A neonatal case of coxsackievirus B3 vertical infection with symptoms of hemophagocytic lymphohistiocytosis. (2020) - Miyoshi, Yasuhiro; Yoshioka, Sachika; Gosho, Hirokazu; Miyazoe, Shoichi; Suenaga, Hideyo; Aoki, Mikihiro; Hashimoto, Kunio
Abstract: Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening syndrome of excessive immune activation that most commonly affects infants. We report the case of a term female neonate with HLH associated with coxsackievirus B3 Infection. Her mother was hospitalized due to high fever 4 days before the delivery. The patient was delivered by vaginal delivery after the induction of labor. She was admitted to the neonatal care unit due to continuous high fever and poor sucking on her 4 th day of life. She developed apnea on her 5 th day of life. Laboratory findings on the patient's 7 th day of life indicated severe thrombocytopenia, liver dysfunction, coagulation abnormality and hyperferritinemia. Coxsackievirus B3 was isolated from all cultured specimens by the PCR method. She received intravenous transfusion of platelets and immunoglobulin. Her platelet count gradually increased to the normal range by her 14 th day of life and she was discharged without any sequelae on her 25 th day of life. To the best of our knowledge, this is the first case report of neonatal HLH associated with a vertical transmission of coxsackievirus B3. Coxsackievirus is an important virus that can cause HLH in neonates. An early diagnosis and timely treatment are crucial.